EVALUATION OF THE RELIABILITY OF ALBATROSS GANTRY CRANE MECHANISMS - STRELBITSKIY, Victor (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Portal cranes are widely used to perform transshipment operations in sea and river areas. Since they are the main link in the technological process, so the performance of Port lines directly depends on their reliable and continuous operation. However, today in the river and sea ports of Ukraine, more than 88% of cranes have fulfilled the standard service life and continue to be operated. Since overtime and long-term operation of metal structures of overhead cranes in the mode of intensive cyclic loading leads to the formation of fatigue defects and subsequent failure of components and accidents. Therefore, ensuring safe and reliable operation is one of the main tasks in the design, modernization and operation of cranes. The analysis of works on the reliability of complex technical systems indicates that the issue of reliability of gantry crane mechanisms, which have been soldered for more than 35 years in seaports, is not sufficiently studied. The purpose of the work is: analysis of failures of mechanisms that occur during the operation of gantry cranes with overtime service life, based on the obtained data, failure and recovery coefficients are calculated.. Operating time affects the mechanical characteristics of materials ambiguously. The aim of the study is to analyze the failure statistics of gantry crane mechanisms with overtime periods to determine, determine the failure and recovery rates. The 30 identical Albatross cranes with a lifting capacity of 16 tons were selected for research, which operate in Grab mode and operate in seaports. Cranes are divided into 3 groups by year of production. The average annual capacity of cranes was 520 thousand tons, according to the warehouse-ship option. From the obtained data, the largest number of failures is observed in the lifting and turning mechanisms, the smallest – in the load lifting mechanism. Thus, the analysis of the results obtained showed that the largest number of failures is observed in the mechanisms of lifting and turning, the smallest – in the mechanisms of lifting the load and moving the crane.